Designing Services for Performance-Part II Continued discussion of the secrets of building and operating a realistic SOA. - Linthicum, David (SOA webservices journal.)
As we discussed last month, performance is often an afterthought when building new systems, including SOAs. We're finding that services and SOAs fall victim to this oversight as well. Indeed, there is a right way and a wrong way to design a service and an SOA. Also, there are things that are out of your control that you must consider during your design.